Privacy and Digital Literacy: Who Is Responsible for the Protection of Personal Data in Serbia? - Stepanović, Ivana (Zbornik Instituta za kriminološka i sociološka istraživanja, 2019)
While privacy laws fail to fully protect personal data in a digital form, especially considering capacities for storing it and the speed of sharing and multiplying it, individuals are responsible for safeguarding their privacy online and taking steps to prevent abuse. However, this requires technical skills and digital literacy, which entails up-to-date knowledge on digital privacy protection and use of a whole set of devices, software, browser extensions and encryption techniques. The General Data Protection Regulation is an attempt to redeem control over privacy protection and divide responsibility between users and other subjects such as data controllers, data processors and other authorities. However, in countries outside the EU where citizens are not protected by the GDPR, the emphasis is much more on individual responsibility. The aim of this paper is to stress out the importance of dividing responsibility for privacy protection among different actors in Serbia.